2021
DOI: 10.1016/j.toxrep.2021.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of traditional healing properties, using the nanotechnology’s advantages: The case of curcumin

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recent investigations focused on DTD of essential oils having healing effects due to either a dual anti-inflammatory/collagenesis-inducing action of the oil itself [ 78 ], or to a synergic antimicrobial and healing action elicited by combination of the essential oil with specific components in the lipid nanocarrier (e.g., oleic acid) [ 79 ]. Very recently, different SLNs and NLCs have been tested along with NEs for DTD of curcumin, a hydrophobic photosensitive phytomolecule, whose anti-inflammatory, antimicrobial, and healing properties have been known for long [ 80 ]. This study revealed that all tested NCs were efficient for photoprotection of the phytopharmaceutical, with NLCs offering the best pharmacological performance, provided the matrix fluidity was tuned for optimized skin occlusion and drug release rate [ 80 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations focused on DTD of essential oils having healing effects due to either a dual anti-inflammatory/collagenesis-inducing action of the oil itself [ 78 ], or to a synergic antimicrobial and healing action elicited by combination of the essential oil with specific components in the lipid nanocarrier (e.g., oleic acid) [ 79 ]. Very recently, different SLNs and NLCs have been tested along with NEs for DTD of curcumin, a hydrophobic photosensitive phytomolecule, whose anti-inflammatory, antimicrobial, and healing properties have been known for long [ 80 ]. This study revealed that all tested NCs were efficient for photoprotection of the phytopharmaceutical, with NLCs offering the best pharmacological performance, provided the matrix fluidity was tuned for optimized skin occlusion and drug release rate [ 80 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…Very recently, different SLNs and NLCs have been tested along with NEs for DTD of curcumin, a hydrophobic photosensitive phytomolecule, whose anti-inflammatory, antimicrobial, and healing properties have been known for long [ 80 ]. This study revealed that all tested NCs were efficient for photoprotection of the phytopharmaceutical, with NLCs offering the best pharmacological performance, provided the matrix fluidity was tuned for optimized skin occlusion and drug release rate [ 80 ]. In line with this, multiple benefits of SLNs/NLCs-mediated delivery of natural and synthetic antimicrobials have been advocated in the recent literature [ 81 , 82 , 83 ], including for fighting multidrug-resistant (MDR) infections [ 84 , 85 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…Curcuma longa L, popularly known as curcumin, turmeric, or saffron, is a plant belonging to the Zingiberaceae family, which is popularly sold as a yellowish powder, mainly from the rhizomes. It is a product widely used in cooking because it is a strong colorant and because of its medicinal activities (Liakopoulou et al 2021 ; Martins et al 2013 ; Zamarioli et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has its maximum absorption at a wavelength of 430 nm, boiling point of 183 °C, low solubility in water, low bioavailability, and reduced chemical stability, being sensitive to various conditions. Due to its low water solubility and susceptibility to factors such as pH, temperature, oxidation, and light, curcumin has limitations in its use (Liakopoulou et al 2021 ; Zamarioli et al 2015 ). It also undergoes extensive first-pass metabolism in the body due to glucuronidation and sulphation in its molecule, which produce derivatives with significantly lower biological activity, and which are more easily eliminated (Vollono et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation